Spatial and Regional Development at Boyolali Regency (Geographical Overview) - Priyana, Yuli (Forum Geografi, 1998)
Geography is a science that studies mutual relationship between nature and the activity of human being through the spatial approach, ecological approach, and regional approach. The spatial approach means studying a variety of location and phenomena in the earth. Boyolali regency has got a variety of physical condition, therefore it causes differently natural resources. It is necessary to implement the approach of spatial order that is intended to design the land suitable for the resources in the area. In the western area, Mounts Merapi and Merbabu are located with their slopes of more than 40% and it is a conservation area. This area is a ground water recharge area. In the lower area, it is a productive area including forest, agriculture, industry, and settlement.